Embryonal carcinoma of an intraabdominal testicular tumor on an undescended testicle: a case report - Suciu, Mihai Domnutiu; Marica, Nucu Alexandru; Oniu, Traian; Tomuta, Andrei Ionut; Badea, Radu (Medicine and Pharmacy Reports, 2020)
Cryptorchidism, as a singular pathology or associated with other dysgenesis syndromes, is one of the main factors of risk for the development of the testicular tumors. Although there are a great number of cases of undescended testicles that are diagnosed and treated during the first 6-12 months of life, there are rare cases of adults who are undiagnosed and untreated from this anomaly, which can present a high risk of malignancy . In this study we present the case of a 36-year-old patient, diagnosed at puberty with left cryptorchidism, untreated, who also hadevidenced a large intraabdominal tumoral mass associated with it. The tumoral mass had its origin in the undescended left testicle. Surgical excision of the tumor and retroperitoneal lymphadenectomy was performed. The histological result revealed embryonal carcinoma, without lymphnode metastasis. Adult patients with untreated cryptorchidism should be thoroughly investigated, as they have a high risk of developing testicular cancer.